Energy storage for renewable energy integration: the case of Madeira Island, Portugal - Miguel, Miguel (2018)
Energy storage has become a crucial issue regarding renewable energy management, even more important in an island system with the inherent fluctuating operation and inaccurate energy forecast. The growth of decentralized generation in an isolated electrical grid means load stability problems and requires energy storage as a potential solution to guarantee safety and reliability standards. The study described in this paper highlights the need to store energy in Madeira island system and evaluate theoperational power dispatch with the introduction of batteries. A simulation tool was developed to quantify the impact of batteries in wind and thermal power plants technologies.